Ethnomathematics study of Pandanwangi village: Schools mathematics instruction in rice farmer activities Pandanwangi - Rani Sugiarni; Tatang Herman; Didi Suryadi; Sufyani Prabawanto; Hutkemri Zulnaidi (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to explore the hidden mathematical concepts behind the rice farming activities of Pandanwangi Cianjur. The research method is qualitative research with an ethnographic approach. The research location is in Pandanwangi Cultural Village, Bunikasih Village, Warungkondang District, Cianjur Regency, West Java. Pandanwangi Cultural Village was deliberately built by the Cianjur Regency Government to further introduce pandanwangi rice, which is the superior local variety of Cianjur Regency. Pandawangi rice farmers' cultural activities contain mathematical concepts that arise when determining seed class, number of seeds, nursery preparation, final seed selection with salt solution, seeding in nurseries, nursery maintenance, preparation of planting land, planting, fertilization in planting areas, planting maintenance, harvest, and post-harvest. The findings of this study show that there are mathematical concepts in agricultural activities on geometric content, including determining points, lines, angles, the area of flat shapes, the similarity of flat shapes, and algebra, including comparisons, percentages, and social arithmetic. The results of the research can be used as a teaching module to facilitate learning for students in the school curriculum.